Laser irradiation prevents root caries: Microhardness and scanning electron microscopy analysis - Cesar P Lepri; Denise T De Castro; Vinícius R Geraldo-Martins; Juliana J Faraoni; Regina G Palma-Dibb (Wolters Kluwer Medknow Publications, 2022)
Context: A promising option for the prevention of dental caries is the use of laser irradiation. Aims: Evaluate the effects of Er:YAG, Nd:YAG, and CO2 laser irradiation, associated or not to 2% sodium fluoride (2% NaF), on root caries prevention. Material and Methods: One hundred and four human root dentin samples were divided in eight groups (n = 13). A 9-mm2-area on each dentin sample was delimited and treated as follows: G1: no treatment (control); G2: 2% NaF; G3: Er:YAG; G4: 2% NaF + Er:YAG; G5: Nd:YAG; G6: 2% NaF + Nd:YAG; G7: CO2; G8: 2% NaF + CO2. When used, the 2% NaF was applied before irradiation for 4 min. The samples were subjected to a 2-week cariogenic challenge, consisted of daily immersion in de-remineralizing solutions for 6 h and 18 h, respectively. Knoop hardness (KHN) were evaluated (10 g and 20 s) at different depths from the dentin surface. The samples (n = 3) were prepared for scanning electron microscopy (SEM). Microhardness data were analysed by one-way analysis of variance (ANOVA) and Fisher's test (α = 5%). Results: The Er:YAG laser group (KHN = 41.30) promoted an increase in acid resistance of the dentin (P < 0.05) when compared to all groups. There was no synergism between laser irradiation and 2% NaF application. Morphological changes were observed after irradiation with all lasers; carbonization and cracks were also observed, except when Er:YAG were used. Conclusions: Er:YAG laser irradiation can safely increase the acid resistance of the dentin surface of the root, since it promoted a significant increase in surface hardness. The application of 2% NaF did not result in a synergistic effect.